DEVELOPMENT DIRECTIONS OF MASTER PROGRAM IN EDUCATIONAL MEASUREMENT - О. Макаренко (Київський національний університет імені Тараса Шевченка, 2016)
Information Society is dynamic and poses new requirements for professional training of specialists. The article presents a SWOT-analysis of the master's program in educational measurement of National Pedagogical Dragomanov University. The main development directions of this program are described, namely: popularization of specialty "011 Science Education (Educational Measurement)"; motivation of students for training and employment on the specialty; improving educational curriculum and programs; improving psycho-pedagogical, organizational learning conditions; improving monitoring of training masters of educational measurement quality; cooperation with employers; international cooperation.Work in each of them involves the immediate and future challenges, priority and perspective tasks. Author substantiates the claim that just systematically working on improving this master's program, it is possible raise it to a new level of development.

У статті наведено SWOT-аналіз магістерської програми з освітніх вимірювань НПУ імені М.П. Драгоманова, виділено основні напрями розвитку даної магістратури, а саме: популяризація спеціальності "011 Науки про освіту (Освітні вимірювання)"; мотивація студентів до навчання та працевлаштування за спеціальністю; удосконалення навчального плану та програм; покращення психолого-педагогічних та ресурсно-організаційних умов навчання; поліпшення системи моніторингу якості підготовки магістрів з освітніх вимірювань; співпраця з роботодавцями; міжнародна співпраця. Деталізовано кожен з напрямів, а також виділено першочергові та перспективні завдання.
НАПРЯМИ РОЗВИТКУ МАГІСТЕРСЬКОЇ ПРОГРАМИ З ОСВІТНІХ ВИМІРЮВАНЬ
Keywords: Магістратура; магістр; магістерська програма; освітні вимірювання; напрями розвитку; SWOT-аналіз; master; master; master program; educational measurement; development directions; SWOT-analysis